Tuning Aqueous Supramolecular Polymerization by an Acid‐Responsive Conformational Switch. Issue 44 (14th July 2020) - Rest, Christina; Philips, Divya Susan; Dünnebacke, Torsten; Sutar, Papri; Sampedro, Angel; Droste, Jörn; Stepanenko, Vladimir; Hansen, Michael Ryan; Albuquerque, Rodrigo Q.; Fernández, Gustavo
Abstract: Besides their widespread use in coordination chemistry, 2, 2'‐bipyridines are known for their ability to undergo cis–trans conformational changes in response to metal ions and acids, which has been primarily investigated at the molecular level. However, the exploitation of such conformational switching in self‐assembly has remained unexplored. In this work, the use of 2, 2'‐bipyridines as acid‐responsive conformational switches to tune supramolecular polymerization processes has been demonstrated. To achieve this goal, we have designed a bipyridine‐based linear bolaamphiphile, 1, that forms ordered supramolecular polymers in aqueous media through cooperative aromatic and hydrophobic interactions. Interestingly, addition of acid (TFA) induces the monoprotonation of the 2, 2'‐bipyridine moiety, leading to a switch in the molecular conformation from a linear ( trans ) to a V‐shaped ( cis ) state. This increase in molecular distortion along with electrostatic repulsions of the positively charged bipyridine‐H + units attenuate the aggregation tendency and induce a transformation from long fibers to shorter thinner fibers. Our findings may contribute to opening up new directions in molecular switches and stimuli‐responsive supramolecular materials. Abstract : Switch and tune ! The trans – cis conformational switching of 2, 2'‐bipyridine in response to acid was exploited to tune supramolecular polymerization processes. For this purpose, the aqueous self‐assembly of a bipyridine‐based linear bolaamphiphile that self‐assembles under standard conditions into cooperative supramolecular polymers was investigated. Interestingly, acid‐triggered protonation of the bipyridine unit induces a molecular conformational change from linear ( trans ) to cis (V‐shaped) that leads to an attenuated supramolecular growth into shorter fibers.